Activities of free and encapsulated Lactobacillus acidophilus LA5 or Lactobacillus casei 01 in processed longan juices on exposure to simulated gastrointestinal tract - Chaikham P. (2014)
Background: Fruit drinks containing probiotics are gaining interest in the global marketplace. For example, longan juice, containing carbohydrate and various bioactive components, is a potentially health-promoting beverage as well as probiotic carrier for human consumption. In this study, high-pressure and thermal processes were applied to eliminate competitive micro-organisms in longan juice prior to the addition of Lactobacillus acidophilus LA5 or Lactobacillus casei 01. The activities of these probiotics in a simulated gastrointestinal tract were also investigated. Results: Encapsulated probiotics could survive in the acidic environment of the stomach and small intestine, while the free cells were completely eliminated. In the colon experiment, the influence of encapsulated L. casei 01 on colon lactobacilli was significantly greater than that of encapsulated L. acidophilus LA5. Both encapsulated probiotics suspended in processed longan juices led to extensive increases in the formation of lactic acid and short-chain fatty acids (SCFA). Acetate was the major SCFA produced by colon bacteria, followed by propionate and butyrate. The discernible clear zone suggested that L. casei 01 provided greater antibacterial activity than L. acidophilus LA5. Conclusion: Both encapsulated probiotics along with processed longan juice led to significant increases in colon lactobacilli, lactic acid and SCFA formation. © 2013 Society of Chemical Industry.